Histopathologic evaluation of effects of systemic Strontium Ranelate application on bone healing after grafting tibial defect - Karabulut, Burak; Tanrisever, Murat; Ozcan, Erhan Cahit; Koksaldi, Irem Semiha; Turgut, Burak; Istek, Ozmen; Dundar, Serkan (Universidad del Zulia, Facultad de Ciencias Veterinarias, 2026)
This study evaluated the effects of different doses of strontium ranelate combined with a bovine-derived deproteinized xenogeneic bone graft on bone healing in a rat defect model. Thirty-five female Sprague Dawley rats were randomly assigned to five groups (n = 7). A healthy control group received no treatment. In all other groups, a standardized 4 mm × 4 mm defect was created in the metaphyseal region of the rat tibia. The defect control group received no additional treatment. In the defect–graft group, the defect was filled with a bovine-derived deproteinized xenogeneic bone graft. In the defect–graft + strontium groups, the defect was filled with the same graft and strontium ranelate was administered by oral gavage at doses of 450 mg/kg or 900 mg/kg, three times per week for eight weeks. All rats were euthanized at the end of the eight-week experimental period. Bone tissues were harvested and processed for histological analysis. Data normality was assessed using the Shapiro–Wilk and Kolmogorov–Smirnov tests. As normality assumptions were not met, group comparisons were performed using the Kruskal–Wallis test followed by Mann–Whitney U post hoc tests. Mean horizontal defect sizes were 0 in the healthy control group, 716.86 in the defect group, 658.57 in the defect–graft group, 604.57 in the defect–graft dose 1 group, and 598.86 in the dose 2 group. Mean vertical values were 0 in the healthy group, 575.14 in the defect group, 596.43 in the defect–graft group, 569 in the dose 1 group, and 503.29 in the dose 2 group. In conclusion, strontium ranelate had a positive effect on bone healing compared to the control group, particularly when combined with grafting. A significant difference was also observed between the defect group and the high-dose group, confirming its beneficial effect on bone healing. © (2025), (Universidad del Zulia). All rights reserved.
Evaluación histopatológica de los efectos de la aplicación sistémica de Ranelate de Estroncio en la curación ósea tras injerto de defecto tibial
Keywords: bone defect; bone grafting; defecto óseo; guided bone regeneration; injerto óseo; Ranelato de estroncio; rat; rata; regeneración ósea guiada; Strontium ranelate; tibia; tibia bone